Narratives of Language Teachers in Teaching English in the Post-Pandemic Era: An Interpretative Phenomenological Analysis (American Journal of Interdisciplinary Research and Innovation, 2024)
The COVID-19 pandemic brought unprecedented challenges to education worldwide, forcing a rapid transition to online learning and fundamentally altering traditional teaching methods. As schools and institutions gradually return to in-person or hybrid models, understanding the narratives of English language teachers is crucial for developing effective pedagogical strategies and policies. This study explored the experiences and perspectives of language teachers in teaching English during the post-pandemic era through an interpretative phenomenological analysis (IPA). The results showed that instructional approaches and developments in technology interact in a complex way. Teachers noted a dramatic change in their pedagogy, stressing the need for adaptability, innovation, and the use of digital resources in language learning. Furthermore, this study discussed the significant changes brought by the crisis to English teachers’ feedback strategies. This research contributes to the understanding of post-pandemic educational landscapes and offers valuable insights for policymakers, educators, and institutions aiming to support language teachers in adapting a new teaching paradigm.